Fuzzy Logic Implementation on Enemy Speed Control to Raise Player Engagement - Abdiansah abdiansah; Anggina Primanita; Frendredi Muliawan (ICON-CSE, 2014)
Shoot em’ up game is the sub-genre of action game. Action game is attractive because the game play usually use the interesting user interface and easily affect human emotion. With the aim to eliminate all the enemy, this kind of game will be boredom the player if the enemy behavior are monotones. This game needs a controller to add dynamic system into the enemy such as the artificial intelligence. Therefore, this paper proposes Fuzzy Takagi Sugeno method that will take several input and give the response as the output. So, the game will manipulate the enemy behavior that make the game more challenging and interesting to be played.